1998
DOI: 10.1128/aem.64.4.1338-1343.1998
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Sensitive Bioassay for Detection of Bacillus cereus Emetic Toxin and Related Depsipeptide Ionophores

Abstract: Of the toxins produced by Bacillus cereus, the emetic toxin is likely the most dangerous but, due to the lack of a suitable assay, the least well known. In this paper, a new, sensitive, inexpensive, and rapid bioassay for detection of the emetic toxin ofB. cereus is described. The assay is based on the loss of motility of boar spermatozoa upon 24 h of exposure to extracts of emetic B. cereus strains or contaminated food. The paralyzed spermatozoa exhibited swollen mitochondria, but no depletion of cellular ATP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(96 citation statements)
references
References 27 publications
5
91
0
Order By: Relevance
“…None of these stains could be loaded into viscosinamide-treated hyphae, however, which in turn indicated that viscosinamide did not induce extensive membrane disorder or destruction. A lipopolypeptide similar to viscosinamide from Bacillus cereus also had no major e¡ects on the membrane integrity in spermatozoa [23]. When extensive pore formation in the membranes could be excluded, an extensive loss of £uorescent stain product from the viscosinamide-treated hyphae could also be ruled out.…”
Section: Hypothesis For the Mechanism Of Viscosinamide On Fungal Growmentioning
confidence: 97%
“…None of these stains could be loaded into viscosinamide-treated hyphae, however, which in turn indicated that viscosinamide did not induce extensive membrane disorder or destruction. A lipopolypeptide similar to viscosinamide from Bacillus cereus also had no major e¡ects on the membrane integrity in spermatozoa [23]. When extensive pore formation in the membranes could be excluded, an extensive loss of £uorescent stain product from the viscosinamide-treated hyphae could also be ruled out.…”
Section: Hypothesis For the Mechanism Of Viscosinamide On Fungal Growmentioning
confidence: 97%
“…Reference strains for the development of the PCR assay were the emetic reference strain F4810/72 [20], three isolates from recent emetic outbreaks in Germany and three emetic isolates from foods (MHI 280, MHI 297, MHI 1305, and MHI 87, MHI 135, MHI 294 [21]), as well as the non-emetic culture collection strains, B. cereus ATCC 14579 T and ATCC 27877, and two non-emetic isolates from foods (MHI 13, MHI 124 [21]). For evaluation of the PCR assay B. cereus strains were obtained from the project culture collection of an ongoing EU project (QLK1-CT-2001-00854).…”
Section: Strainsmentioning
confidence: 99%
“…MALDI-TOF-MS was performed as described previously [18]. ESI-MS/MS data were collected as described previously [19]. Samples were dissolved in 50% aqueous methanol containing 1% formic acid before injection into the mass spectrometer.…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…The inhibition of the motility and the acrosome reaction of boar spermatozoa caused by toxins, damage to plasma membrane, swelling of mitochondria and loss of cellular ATP and NADH were analyzed as described elsewhere [3,19,21].…”
Section: Bioassaymentioning
confidence: 99%